Debate - Achievements of the Trafficking Protocol: Perspectives from the former UN Special Rapporteur on Trafficking in Persons - Ezeilo, Joy N (Anti-Trafficking Review, 2015)
The United Nations (UN) Protocol to Prevent, Suppress and Punish Trafficking in Persons, Especially Women and Children, Supplementing the UN Convention against Transnational Organized Crime, 2000 (Trafficking Protocol), is a watershed in galvanising the global movement against human trafficking. Thanks to the Protocol, international and regional bodies, along with civil society groups, have become involved in researching the issue and supporting anti-trafficking efforts; and states have begun to introduce new laws and policies aimed at criminalising trafficking, protecting victims and preventing future trafficking.[1] [1] J N Ezeilo, ‘First decade of the mandate of the Special Rapporteur on trafficking in persons, especially women and children’, A/HRC/26/37, UN, 2014.